Ethyl cyclopentenolone suppresses browning in fresh-cut potatoes by regulating PPO activity, phenylpropanoid metabolism and antioxidant defense - Pingping Fan; Shaohe Jiao; Xiaoyong Chang; Xiongfeng Zhang; Junping Liu; Wei Liu; Lei Zhou (Postharvest Biology and Technology, 2026)

A preliminary single-cell map of endometriosis suggests roles for fibroblast metabolism and macrophage polarization in disease progression - Xiurong Cao; Hui Tao; Xiang Fan; Yifei Wang; Jia Yang; Wenbo Zhou; Pingping Xue; Pengfeng Zhu (Functional & Integrative Genomics, 2026)

Inhibition of maltol on enzymatic browning in potato: Combined effects on PPO activity, substrate biosynthesis, and oxidative stress - Xiaoyong Chang; Pingping Fan; Zhaorui Liang; Xing Lu; Junping Liu; Wei Liu; Xiongfeng Zhang; Shaohe Jiao; Lei Zhou (Food Chemistry, 2026)

Cold plasma technology for the modification and quality control of food components via exogenous RONS: Mechanisms, strategies, and future prospects - Xiaotong Fan; Jiabao Ni; Yanxiang Bi; Shiye Luo; Pingping Dong; Shenyuan Quan; Jiaxin He; Xiaoming Fang (Food Bioscience, 2026)

Tumor microenvironment-programmed dual-responsive nanoprobes enable fluorescence/photoacoustic imaging-guided enhanced tumor phototherapy by blocking protective autophagy - Jie Zhao; Haiyi Zhang; Juan Lu; Min Fan; Pingping Jie; Zhengzhen Yuan; Yingying Qi; Qin Zhang; Jian Shu; Yongcan Guo; Zhijin Fan; Lei Zhang (Chemical Engineering Journal, 2026)

Nitrogen doping engineering of Ru nanoparticles/Mo2C MXene for efficient hydrogen production via NH3BH3 hydrolysis - Zhenluo Yuan; Fei Ya; Yang Shi; Shuyan Guan; Pingping Wang; Pei Liu; Shiqian Zhao; Qiuming Peng; Yanping Fan; Baozhong Liu (Chemical Engineering Journal, 2026)

Magma degassing controlling the formation of porphyry copper deposits: A dynamic analysis through numerical modeling - Fan Xiao; Changhua Xie; Pingping Zhu; Qiuming Cheng (Journal of Geochemical Exploration, 2026)

Temperature-dependent effects of lanthanum-modified bentonite on sediment nitrogen removal processes and the underlying microbial mechanisms - Penglong Wang; Jiehua Wang; Pingping Zhang; Zhiqiang Jiao; Xiuling Bai; Zhonghua Zhao; Jinyue Fan; Songwei Zhang; Bing Zhao; Xiubo Ren; Huidian Dou; Wenhao Bai (Water Research, 2026)

Phosphorus limitation drives the deterministic assembly of dissolved organic matter and microbial activity in surface waters of urban lakes - Wei Yu; Pingping Fan; Haiquan Yang; Wenhao Li; Guomin Han; Jifei Hou; Rui Liang; Jingan Chen; Jie Li; Xuede Li (Organic Geochemistry, 2026)

Soil hydraulic pedotransfer functions for estimating saturated hydraulic conductivity: a deep symbolic regression approach with mean shift clustering - Cheng Zhang; Zhongwang Wei; Wei Shangguan; Fan Bai; Wenzong Dong; Qiyun Xiao; Hongwei Zhao; Pingping Liu; Qingliang Li; Yongjiu Dai (Journal of Hydrology, 2026)

Multi-view field deep learning and data augmentation for heavy metals concentrations prediction in marine sediments based on visible and near-infrared spectroscopy - Xueying Li; Wenzhuo Li; Kai Li; Huimin Qiu; Pingping Fan (Marine Pollution Bulletin, 2026)

Vertical Distribution and Controls on Heavy Metal(loid)s in Shallow Fissure Soils of Karst Geochemical Background Regions - Liang Tai; Yong Niu; Jia Chen; Gang Li; Pingping Fan; Feng Zhang; Tingjun Tan; Kaiqian Shi (Water, Air, & Soil Pollution, 2026)

OSMAC-activated and GNPS-guided investigation of alkaloids from an endophytic fungus Aspergillus sp. FH-1 of Valeriana officinalis L. - Hao Fan; Pingping Wu; Xin Wang; Yuze Li; Chong Deng; Wei Wang; Xiaomei Song; Xin Zhang; Dongdong Zhang (Biochemical Systematics and Ecology, 2026)

Long-term monitoring reveals scale-dependent decoupling of waterbird diversity at a tropical island flyway node - Miaomiao He; Yufeng Lin; Cheng Cheng; Zhiqin Zhou; Pingping Guo; Xin Fan; Wenqing Wang (Journal of Environmental Management, 2025)

Activating V4+/V5+ redox couple in polyanion lattice engineered Na3.1V2(PO4)2.9(SiO4)0.1-CNT by synergistic ionotronic strategy - Anyang Yu; Qi Fan; Zilong Fang; Tian Jiang; Xinxin Wang; Xiedie Zhao; Xiaoshuang Ma; Pingping Sun; Gang Li; Shijun Yuan; Haiyang Zhang; Yining Wang; et al. (Chemical Engineering Journal, 2025)

The effect of autophagy activation on apoptosis and myofibrillar structural proteins during the post-mortem storage of Esox lucius - Xuemei Fan; Yibo Liu; Xin Guo; Yabo Wei; Pingping Liu; Hui Li; Xin Chen; Xiaorong Deng; Yongdong Lei; Jian Zhang (Food Chemistry, 2025)

Antifungal activity of volatile organic compounds produced by Weizmannia coagulans CGMCC 9951 on Ceratocystis fimbriata in postharvest sweet potatoes and its potential biocontrol - Pingping Tian; Yuanyuan Mi; Jia Xu; Ying Wu; Lina Zhao; Shanshan Tie; Jie Zhang; Qiuxia Fan; Shaobin Gu (International Journal of Food Microbiology, 2025)

Unexpectedly stable soil organic carbon in tidal marshes under combined nitrogen loading and increased inundation compared to individual effects - Tianning Fan; Jiafang Huang; Guopeng Liang; Shengen Liu; Dehong Hu; Lifei Su; Yi Liu; YuanBin Cai; Shihua Li; Pingping Guo; Min Luo; Chuan Tong (Limnology and Oceanography, 2025)
Tidal marshes serve as critical carbon (C) sinks, yet face increasing threats from global environmental changes. While previous research has documented how nitrogen (N) loading and sea‐level rise affect total C pools individually, their impacts on soil organic carbon (SOC) stabilization remain critically underexplored, particularly when these factors co‐occur in tidal marsh ecosystems. Through a 3‐yr field experiment, we analyzed how these factors, alone and combined, impact SOC stabilization by examining SOC fraction dynamics. Results showed that N loading increased particulate organic carbon (POC) by 18% and decreased mineral‐associated organic carbon (MAOC) by 13%, reducing SOC stabilization. Conversely, increased inundation raised MAOC by 31% and decreased POC by 19%, promoting SOC stabilization. The decreased MAOC under N loading stemmed from reduced fungal necromass C, while the increased POC related to lower phenol oxidase activity. In contrast, with increased inundation, MAOC rose due to iron‐bound organic C (Fe‐OC) accumulation, while POC declined from increased phenol oxidase activity. When both factors were applied together, SOC stabilization remained at control levels. This occurred because the combined effect maintained oxidative enzyme activities and thus retained POC levels. The simultaneous reduction in fungal necromass C and enhancement of Fe‐OC associations established complementary mechanisms that maintained MAOC at levels equivalent to control. Our findings reveal that N loading and increased inundation drive contrasting patterns of SOC stabilization, while their combination produces uniquely stabilized C dynamics. This insight challenges single‐factor predictions and underscores the importance of multi‐factor experiments in understanding ecosystem responses under concurrent global change scenarios.

Enhanced stabilization and curcumin delivery by covalent NaCas-EGCG modified proso millet protein nanoparticles in Pickering emulsions - Yuting Fan; Jing Ren; Xinyi Li; Pingping Zhang; Yang Yao; Xiuzhu Yu; Shuang-kui Du (Food and Bioproducts Processing, 2025)

Development of a novel LBL@DHBA/Cu-MOF coating on titanium implants to accelerate early osseointegration by promoting neural-vascular-bone coupling regeneration - Peng Hua; Xiaoyi Pan; Jiming Liu; Xuemei Chen; Manjuan Li; Yan Guo; Xuan Li; Pengyuan Leng; Guoyong Fan; Mengjiao Zheng; Kai Yu; Pingping Ma; et al. (Chemical Engineering Journal, 2025)

Complete genome sequence and genome organization of Ficus pumila-associated virus, a new putative member of the family Tymoviridae - Mengze Guo; Pingping Sun; Xudong Fan; Jianwei Guo; Lei Zhang; Zhengnan Li (Archives of Virology, 2025)

Human-induced N-P imbalances will aggravate GHG emissions from lakes and reservoirs under persisting eutrophication - Wei Yu; Fali Liu; Xianglan Jiao; Pingping Fan; Haiquan Yang; Yongmei Zhang; Jie Li; Jingan Chen; Xuede Li (Water Research, 2025)

Heavy metal concentrations prediction of marine sediments by visible-near infrared spectroscopy based on attention mechanism - Xueying Li; Huimin Qiu; Aizhong Ding; Pingping Fan (Journal of Hazardous Materials, 2025)

Investigation of the interaction between chrysin, apigenin, and luteolin with HMGB1 using integrated multi-spectroscopy and molecular docking methods - Yi Kuang; Yiming Xie; Cailing Tan; Junyi Ye; Pingping Shen; Richa Raj; Fan Zhang; Jian Zhang (Food Bioscience, 2025)

Spectral Analysis of Dissolved Organic Carbon in Seawater by Combined Absorption and Fluorescence Technology - Xuan Cao; Feng Xiong; Yang Wang; Haikuan Ma; Yanmin Zhang; Yan Liu; Xiangfeng Kong; Jingru Wang; Qian Shi; Pingping Fan; Yunzhou Li; Ning Wu (Journal of Marine Science and Engineering, 2024)
Dissolved organic carbon refers to soluble carbon substances in water bodies and can be used as an important indicator for water pollution. Spectroscopic detection is commonly used to detect dissolved organic carbon in seawater. However, independent spectral methods are susceptible to interference, and insufficient extraction of the data features can occur. Accordingly, this study introduces a multisource spectral fusion method that relies on a combination of principal component analysis and convolutional neural networks to construct the detection model. The Bayesian correction method is used for calibration, and the dissolved organic carbon content of 10 groups of unfiltered seawater samples is analyzed. Correcting the spectral data acquired from samples containing impurities significantly improved the linear correlation coefficient R2 of dissolved organic carbon from 0.8891 to 0.9838. Similarly, the mean absolute error was significantly reduced from 15.33% to 3.24%, while the individual absolute error was effectively controlled, remaining within 9%. The obtained results show that the developed method effectively integrates the ultraviolet absorption and fluorescence spectral data and overcomes interference from other substances using the Bayesian correction method. Overall, this provides a highly accurate detection system with potential applications in monitoring the marine environment.

Nitrogen deposition enhances accumulation of microbial and plant-derived carbon in forest soils: a global meta-analysis - Chenying Wang; Xiaoyan Li; Meng Zhang; Zichen Han; Yun Xia; Pingping Lian; Liuming Yang; Kai Yue; Yuexin Fan (Plant and Soil, 2024)

Distribution mechanisms of soil surface erosion and underground leakage in karst areas of China: A systematic, quantitative review - Jia Chen; Pingping Fan; Feng Zhang; Tingjun Tan; Nufang Fang; Zeyan Wu; Zhongwu Li; Yaojun Liu (CATENA, 2024)

Unravelling the structure-performance relationship of zeolite Beta in the catalytic cracking of low-density polyethylene by proposing gasoline factor as the descriptor - Yi Wang; Hao Wu; Yuanhao Liu; Wansheng Wang; Pingping Wu; Hongchao Fan; Zhihui Liu; Peng Bai; Zifeng Yan (Fuel, 2024)

Phosphorus addition enhances heterotrophic respiration but reduces root respiration in a subtropical plantation forest - Yun Xia; Benjamin L. Turner; Yiqing Li; Pingping Lian; Zhijie Yang; Yuexin Fan; Liuming Yang; Yusheng Yang (Science of The Total Environment, 2024)

Identification of a novel waikavirus infecting Pittosporum tobira in China - Mengze Guo; Lei Zhang; Xudong Fan; Pingping Sun; Jianwei Guo; Zhengnan Li (Archives of Virology, 2024)

NIR-photocatalytic LDHB-mimetic CuS@ZnS nanoenzyme regulates arthritis microenvironment through lactate oxidation and hydrogen evolution - Dezhi Lu; Fan Wu; Kangming Chen; Wentao Li; Pingping Zhang; Yutong Hou; Yingze Su; Weixi Liu; Tianchang Wang; Yihao Liu; Chenglan Huang; Shuo Chen; et al. (Chemical Engineering Journal, 2024)

Effect of liquid nitrogen spray quick-freezing technology on the quality of bamboo shoots, Dendrocalamus brandisii from Yunnan Province, China - Zhenmei Fan; Hui Shen; Tenggen Hu; Lijuan Yu; Yujuan Xu; Jijun Wu; Pingping Shi; Xianliang Song; Yuanshan Yu (Journal of Food Engineering, 2024)

Optimizing soil carbon content prediction performance by multi-band feature fusion based on visible near-infrared spectroscopy - Xueying Li; Pingping Fan; Huimin Qiu; Yan Liu (Journal of Soils and Sediments, 2024)

Population dynamics of a stoichiometric aquatic tri-trophic level model with fear effect - Pingping Cong; Meng Fan; Xingfu Zou (Mathematical Biosciences, 2024)

Increase in iron-bound organic carbon content under simulated sea-level rise: A “marsh organ” field experiment - Dehong Hu; Wenjing Lan; Min Luo; Tianning Fan; Xin Chen; Ji Tan; Shihua Li; Pingping Guo; Jiafang Huang (Soil Biology and Biochemistry, 2023)

Efficient path planning for AUVs in unmapped marine environments using a hybrid local–global strategy - Wenlong Meng; Ya Gong; Fan Xu; Pingping Tao; Pengbo Bo; Shiqing Xin (Ocean Engineering, 2023)

Hyperspectral images classification of small sample based on the strategy of sample enlargement by superpixel pair method - Xueying Li; Pingping Fan; Zongmin Li; Huimin Qiu; Guangli Hou; Guangyuan Chen; Guoxing Ren (International Journal of Remote Sensing, 2023)

Realization of highly deformable freestanding borophene hybrid film for flexible energy storage device - Jiali Yu; Zhimin Fan; Fei Yu; Hang Zhao; Pingping Yao; Shengnan Chen; Haiyan Yang; Caizhen Zhu; Jian Xu (Chemical Engineering Journal, 2023)

Incorporating biotic phosphorus-acquisition strategies into soil phosphorus transformation under long-term salinization in a tidal wetland - Tianning Fan; Min Luo; Ji Tan; Dehong Hu; Xin Chen; Jiafang Huang; Shihua Li; Pingping Guo; Ji Chen (CATENA, 2023)

Soil carbon content prediction using multi-source data feature fusion of deep learning based on spectral and hyperspectral images - Xueying Li; Zongmin Li; Huimin Qiu; Guangyuan Chen; Pingping Fan (Chemosphere, 2023)

Immunomodulatory Mechanisms and Therapeutic Potential of Mesenchymal Stem Cells - Guoqiang Yang; Xuehui Fan; Yingchun Liu; Pingping Jie; Maryam Mazhar; Yong Liu; Nathupakorn Dechsupa; Li Wang (Stem Cell Reviews and Reports, 2023)
Mesenchymal stem cells (MSCs) are regarded as highly promising cells for allogeneic cell therapy, owing to their multipotent nature and ability to display potent and varied functions in different diseases. The functions of MSCs, including native immunomodulation, high self-renewal characteristic, and secretory and trophic properties, can be employed to improve the immune-modulatory functions in diseases. MSCs impact most immune cells by directly contacting and/or secreting positive microenvironmental factors to influence them. Previous studies have reported that the immunomodulatory role of MSCs is basically dependent on their secretion ability from MSCs. This review discusses the immunomodulatory capabilities of MSCs and the promising strategies to successfully improve the potential utilization of MSCs in clinical research. Graphical Abstract

Effects of LED spectrum on circadian rhythmic expression of clock genes and Aanat2 in the brain of juvenile European seabass (Dicentrarchus labrax) - He Ma; Songtao Liu; Pingping Wei; Fan Fei; Jilong Ren; Mingyun Dai; Zhen Ma; Ying Liu (Frontiers in Marine Science, 2023)
The circadian rhythm is a physiological phenomenon that occurs in various organisms with a cycle of about 24 hours. Light is one of the important environmental factors affecting biological rhythm. To clarify whether a shift in light spectrum can influence the circadian expression in fish brain, a total of 175 European seabasses [body weight: 32.5 ± 0.71) g; body length: (13.78 ± 0.35) cm] were exposed to white light (WL), red light (RL), yellow light (YL), green light (GL) or blue light (BL). After 50 days of exposure, circadian expressions of four core clock genes ( Clock, Bmal1, Per2, Cry1 ) and Aanat2 gene in brain were examined. The results showed that the temporal expression patterns of positive clock gens ( Clock and Bmal1 ) showed increases during the scotophase and decreases during the photophase, with peaks near the middle of the darkness. Clock gene expression showed a stable circadian rhythm (R 2 = 0.578-0.824, P =0.000- 0.027) in all light groups while Bmal1 showed circadian rhythm in WL, GL and RL, not in BL and YL. Daily expression patterns of the negative clock genes oscillated in the opposite phase from the positive clock genes, showing increasing mRNA levels during the light, decreases during the dark, and peaks near the shift from night to day, except Per2 in RL and Cry1 in BL. Compared with WL, the acrophases of Clock and Bmal1 were delayed under all light treatments (BL: + 3.7h, +6.73h; RL: +2.4h,+1.35h; YL: + 4.94h, 2.00h; GL: +0.05, +0.16h). Cry1 showed advanced acrophase under all light treatments (BL: -10.74 h, GL: -3.81 h, RL: -3.93 h, YL: -7.56 h) but Per2 showed delayed acrophase in all light treatments (GL: +0.86 h, RL: +10.35 h, YL: +9.62 h), except in BL (-0.43 h). The acrophase of Aanat2 was advanced by all monochromatic light, the Aanat2 level was significantly increased in RL compared with other light treatment. Therefore, the results indicate that RL may regulate the expression of Aanat2 gene by affecting the expression of clock gene in fish brain. Spectrum can affect the biological clock system of fish, and unreasonable spectrum may disturb the rhythm of gene expression of biological clock of fish. Under the irradiation of light spectrum, some clock genes still maintain obvious circadian oscillation, while the rhythm of some clock genes is not obvious and may be destroyed. Our findings suggest a primary role of light spectrum information to the fish brain circadian system.

Cytotoxicity and pro-inflammatory effect of polystyrene nano-plastic and micro-plastic on RAW264.7 cells - Xiaoxia Wang; Xiao-Min Ren; Huan He; Fan Li; Kunqian Liu; Fenqing Zhao; Huixiang Hu; Pingping Zhang; Bin Huang; Xuejun Pan (Toxicology, 2023)

Cellular Heterogeneity Facilitates the Functional Differences Between Hair Follicle Dermal Sheath Cells and Dermal Papilla Cells: A New Classification System for Mesenchymal Cells within the Hair Follicle Niche - Yuyang Gan; Hailin Wang; Lijuan Du; Kaitao Li; Qian Qu; Weiwen Liu; Pingping Sun; Zhexiang Fan; Jin Wang; Ruosi Chen; Zhiqi Hu; Yong Miao (Stem Cell Reviews and Reports, 2022)

Analysis and Model Comparison of Carbon and Nitrogen Concentrations in Sediments of the Yellow Sea and Bohai Sea by Visible-Near Infrared Spectroscopy - Huimin Qiu; Pingping Fan; Guangli Hou; Xueying Li; Yinglong Wang (Bulletin of Environmental Contamination and Toxicology, 2022)

Addition of humic acid accelerates the growth of Euglena pisciformis AEW501 and the accumulation of lipids - Panpan Fan; Pingping Xu; Yuxuan Zhu; Xiaojie Tu; Gaofei Song; Yanxia Zuo; Yonghong Bi (Journal of Applied Phycology, 2022)

Dietary exposure of general Chinese population to fatty acid esters of 3-monochloropropane-1, 2-diol (3-MCPD) from edible oils and oil-containing foods - Xia Cui; Lei Zhang; Pingping Zhou; Zhaoping Liu; Sai Fan; Dajin Yang; Jianwen Li; Qing Liu (Food Additives & Contaminants: Part A, 2021)

The origin of arc basalts: New advances and remaining questions - Yigang Xu; Qiang Wang; Gongjian Tang; Jun Wang; Hongyan Li; Jinsheng Zhou; Qiwei Li; Yue Qi; Pingping Liu; Lin Ma; Jingjing Fan (Science China Earth Sciences, 2020)

Depositional environments of limestones from the Taiyuan Formation in the North China Block interpreted from REE proxies - Dawei Lv; Wengui Fan; John I. Ejembi; Dun Wu; Dongdong Wang; Zengxue Li; Junpeng Li; Pingping Li (Carbonates and Evaporites, 2020)

A cytokinin-activation enzyme-like gene improves grain yield under various field conditions in rice - Changgui Wang; Guokui Wang; Yang Gao; Guihua Lu; Jeffrey E. Habben; Guanfan Mao; Guangwu Chen; Jiantao Wang; Fan Yang; Xiaoqiang Zhao; Jing Zhang; Hua Mo; et al. (Plant Molecular Biology, 2020)

Variations in silicate concentration affecting photosynthetic carbon fixation by spring phytoplankton assemblages in surface water of the Strait of Malacca - Gang Li; Qiang Lin; Pingping Shen; Guangyan Ni; Xingyu Song; Shengfu Wang; Yanzhi Fan; Liangmin Huang; Yehui Tan (Acta Oceanologica Sinica, 2013)

Slow decomposition and limited nitrogen release by lower order roots in eight Chinese temperate and subtropical trees - Yanmei Xiong; Pingping Fan; Shenglei Fu; Hui Zeng; Dali Guo (Plant and Soil, 2013)

Nitrogen dynamics differed among the first six root branch orders of Fraxinus mandshurica and Larix gmelinii during short-term decomposition - Pingping Fan; Youxu Jiang (Journal of Plant Research, 2010)

Slow decomposition of lower order roots: a key mechanism of root carbon and nutrient retention in the soil - Pingping Fan; Dali Guo (Oecologia, 2010)